Development of helical coil based fluidic diode pump for liquid pumping. (5th July 2017) - Manavalan, Balamurugan; Pandey, Niranjan K.; Kumar, Shekhar; Mudali, Kamachi U.; Joshi, Jyeshtharaj B.
Abstract : The main selection criterion for pumps in reprocessing applications is the absence of any moving parts or the moving parts not having any direct contact with the process fluid. There are different types of fluidic pumps such as vortex diode, reverse flow diode, etc. In this work, a new design of helical coil fluidic pump has been developed and demonstrated. Helical coils are widely used in process industries as heat exchangers, reactors, motionless mixers, etc. It is for the first time that the authors are proposing the use of helical coil as a fluidic pump based on its inherent property of high pressure drop as compared to a straight tube. The main objective of this work is to develop an alternate pumping system for reprocessing applications to replace the conventional air lift pump. The helical coil based fluidic diode pump was made up of SS 304 seamless pipe (pipe inner diameter is 9.5 mm) with a 36 mm diameter of helical coil and pitch of 14 mm. In this work, friction factor for the given helical coil was measured from pressure drop experiments. This information was also useful for understanding the transition of the laminar to turbulent region. In order to propose the operating region, the pumping capacity was measured for the helical coil based fluidic pump at different operating conditions. Experimental results show that the proposed hardware is able to pump up to 54 dm 3 /h. Recommendations have been made for proposing an optimum design.